Pengaruh Sikap, Kontrol Perilaku dan Kemudahan Penggunaan Terhadap Minat Penggunaan Sistem Informasi Akuntansi Berbasis E-Commerce - Ni Luh Ayu Rimayanti; Ni Wayan Alit Erlina Wati; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2026)
The rapid advancement of digital technology has encouraged the implementation of e-commerce-based accounting information systems to enhance efficiency and accuracy in managing financial information. Nevertheless, students’ interest in optimally utilizing these systems is still relatively low, despite living in an increasingly digital environment. This issue becomes important to examine, particularly among students of Universitas Hindu Indonesia who are engaged in economics and accounting-related fields of study. This research aims to examine the effect of Attitude, Behavioral Control, and Perceived Ease of Use on the Interest in Using E-Commerce-Based Accounting Information Systems. The study applies a quantitative approach involving 338 respondents selected using the Slovin formula. Data collection was conducted through questionnaires, while data analysis utilized multiple linear regression assisted by the SPSS application. The findings reveal that Attitude, Behavioral Control, and Perceived Ease of Use positively and significantly influence the Interest in Using E-Commerce-Based Accounting Information Systems. These results indicate that students are more likely to use the system when they possess positive attitudes, strong behavioral control, and perceive the system as easy to operate.